Experimental evidence for trait utility of gill raker number in adaptive radiation of a north temperate fish. (25th May 2013) - Roesch, C.; Lundsgaard‐Hansen, B.; Vonlanthen, P.; Taverna, A.; Seehausen, O.
Abstract: North temperate fish in post‐glacial lakes are textbook examples for rapid parallel adaptive radiation into multiple trophic specialists within individual lakes. Speciation repeatedly proceeded along the benthic–limnetic habitat axis, and benthic–limnetic sister species diverge in the number of gill rakers. Yet, the utility of different numbers of gill rakers for consuming benthic vs. limnetic food has only very rarely been experimentally demonstrated. We bred and raised families of a benthic–limnetic species pair of whitefish under common garden conditions to test whether these species (i) show heritable differentiation in feeding efficiency on zooplankton, and (ii) whether variation in feeding efficiency is predicted by variation in gill raker numbers. We used zooplankton of three different size classes to investigate prey size dependency of divergence in feeding efficiency and to investigate the effect strength of variation in the number of gill rakers. Our results show strong interspecific differences in feeding efficiency. These differences are largest when fish were tested with the smallest zooplankton. Importantly, feeding efficiency is significantly positively correlated with the number of gill rakers when using small zooplankton, also when species identity is statistically controlled for. Our results support the hypothesis that a larger number of gill rakers are of adaptive significance for feeding on zooplankton and provide one of the first experimental demonstrations of trait utility of gill raker number when fish feed on zooplankton. These results are consistent with the suggested importance of divergent selection driven feeding adaptation during adaptive radiation of fish in post‐glacial lakes.